If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 23 = -5 Reorder the terms: 23 + 8x = -5 Solving 23 + 8x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 8x = -5 + -23 Combine like terms: 23 + -23 = 0 0 + 8x = -5 + -23 8x = -5 + -23 Combine like terms: -5 + -23 = -28 8x = -28 Divide each side by '8'. x = -3.5 Simplifying x = -3.5
| -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 8x+23=-5 | | 16x-14=3(4x-5)+4x+1 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -184=-8(7-8n) | | 7+2(3c+1)=6c+9 | | 7-2n=n+4 | | 7+2(3c+1)=6c+9 | | 7m-(9-4m)=3(m-11) | | 8x+23=-5 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 2x-5=7x-105 | | 7+2(3c+1)=6c+9 | | 8x+4y+2z=16 | | -218=2r-8(6-4r) | | 8m-3(4-2m)=6(m+1)-2 | | x+2X+2X+2=27 | | -5-(m+8)+6m=4(m+2) | | 2(2x-1)-27= | | -2(3t-4)+4t=2t-5 | | 140=-7(1+7p) | | 3m+2(m+2)=13-(2m-5) | | 3m+2(m+2)=13-(2m-5) | | 14x+35=315 | | X*0.6666666666666667=34 | | 49+-1x=129+-9x | | -3+6x-x=42 | | 4+3x=4(4x+6) | | -4(v+4)=9v-3 | | 6x+7(x+1)=20 | | t=5.3(4)+9.5 | | -2+.66x=8 |